2010
DOI: 10.1002/ep.10445
|View full text |Cite
|
Sign up to set email alerts
|

Techno‐economics of the production of mixed alcohols from lignocellulosic biomass via high‐temperature gasification

Abstract: This techno-economic study investigates the production of mixed alcohols from lignocellulosic biomass using an entrained flow slagging gasifier. Similar analyses for 2000 dry tonne per day plants have been performed at the National Renewable Energy Laboratory using indirect, and direct dry ash gasifiers. The use of a high-temperature entrained flow gasifier differs from the previous studies because it eliminates equipment for tar and methane reformation. The conversion targets for tar reforming in the previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 41 publications
2
48
0
Order By: Relevance
“…The production cost is dependent on the conversion technology, enzyme loading, feedstock, allocation methods, and plant sizes [21,24]; thus, production costs may vary, if different conversion methods, allocation, and plant sizes are considered. Although the cost of lignocellulosic ethanol is reported to be vary widely [22,24,[49][50][51][52], the production costs estimated in this study are found to be reasonable and comparable with other studies. …”
Section: Production Costsupporting
confidence: 81%
See 1 more Smart Citation
“…The production cost is dependent on the conversion technology, enzyme loading, feedstock, allocation methods, and plant sizes [21,24]; thus, production costs may vary, if different conversion methods, allocation, and plant sizes are considered. Although the cost of lignocellulosic ethanol is reported to be vary widely [22,24,[49][50][51][52], the production costs estimated in this study are found to be reasonable and comparable with other studies. …”
Section: Production Costsupporting
confidence: 81%
“…A wide variation in ethanol yield from Miscanthus [39,[44][45][46], feedstock, and enzyme cost are also stated [50,53]. The potential hotspots are identified to be feedstock, pre-treatment, and fixed cost in case of energy consumption, emission, and production cost, respectively.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…A wide variation of production cost was also reported by several authors where the lignocellulosic ethanol production by thermochemical gasification processes were modeled (most of the studies modeled with Aspen Plus software) to estimate the production cost. The production cost varied from 0.27-1.25 $/L [24,66,75,[78][79][80][81][82]100]. The feedstock and capital cost are identified to be main hotspots [80,82].…”
Section: Lca Of Ethanol Produced From Biosyngasmentioning
confidence: 99%
“…The production cost varied from 0.27-1.25 $/L [24,66,75,[78][79][80][81][82]100]. The feedstock and capital cost are identified to be main hotspots [80,82]. Although most of the theoretical studies (modeled with Aspen Plus software) noted that the thermochemical conversion of lignocellulosic …”
Section: Lca Of Ethanol Produced From Biosyngasmentioning
confidence: 99%
“…Techno-economic assessments of the thermochemical production of ethanol from biomass gasification and catalytic synthesis have been published [1][2][3][4][5][6]. These works assumed a KCoMoS 2 catalyst with a target performance to be achievable in the short term [1].…”
Section: Introductionmentioning
confidence: 99%